Macrofungal diversity in three protection forests of Sambas District, West Kalimantan, Indonesia - LAILI FITRI YENI; MAS AKHBAR FATURRAHMAN; AHMAD ALOY SAPUTRA; KHAIRI KHAIRI; RISKA MAULIDYA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Yeni LF, Faturrahman MA, Saputra AA, Khairi, Maulidya R. 2025. Macrofungal diversity in three protection forests of Sambas District, West Kalimantan, Indonesia. Biodiversitas 26: 4309-4323. The Gunung Pemangkat Protection Forest (GPPF), Gunung Majau Protection Forest (GMPF), and Gunung Sekadau Protection Forest (GSPF) in Sambas District, West Kalimantan, Indonesia, are three tropical rainforests whose macrofungal communities remain undocumented. This study aimed to investigate the previously unexplored macrofungal diversity in GPPF, GMPF, and GSPF. Field surveys were conducted along zigzag transects to systematically record macrofungi. Identification was based on macromorphological features and confirmed with online taxonomic databases. Environmental factors were measured to characterize habitat conditions. Subsequently, the spatial distribution of macrofungi was analyzed and mapped. A total of 94 macrofungal species from 30 families across Ascomycota and Basidiomycota were recorded: 44 species from 23 families in GPPF, 42 from 20 families in GMPF, and 54 from 22 families in GSPF. Polyporaceae was the most species-rich family. Most taxa were saprophytic and predominantly associated with wood debris, while a smaller number occurred on decomposing litter and soil. Parasitic and mutualistic types were recorded only occasionally. Favorable environmental factors—warm temperatures, high humidity, slightly acidic soils, and low light intensity—likely supported macrofungal growth. Spatial analysis revealed a clumped distribution pattern associated with microhabitat variability and substrate availability. More than half of the macrofungi identified at the species level possess nutritional or medicinal value, underscoring their socio-economic importance. This study provides the first inventory of macrofungi in these forests, filling a critical knowledge gap in the region and extending beyond previous reports from Borneo, especially West Kalimantan. Systematic sampling in GPPF, GMPF, and GSPF revealed a broader spectrum of diversity and confirmed these forests as key reservoirs of macrofungal richness. The findings establish a critical baseline for ecological studies and emphasize the importance of conservation in these protection areas. More broadly, the study advances understanding of tropical fungi in Southeast Asia and underscores their role in long-term biodiversity management.